Modelamiento predictivo de vibraciones en campo lejano para el control de daño en chancadora primaria y poza pop en la unidad minera lagunas norte - Bobadilla Velásquez, Yosselyn Talhía (2007)
At the Lagunas Norte Unit, of the Barrick Misquichilca Mining Company, the plan for the start of 2017 is to expand the dam by the Dafne zone. According to medium-term planning, for the beginning of 2017 comes with the extension of the Tagus by the area of DAFNE. As part of this expansion, blast fronts are closer to two major mine structures;The primary crusher and the Poza. Therefore, in order to minimize the level of vibrations and avoid damage to these two installations, modeling and vibration simulations were performed in order to optimize factors that affect the level of vibrations, including the most important, Delay, time between holes, output sequence, etc. Modeling and blasting simulations with Orica Mining Services' ShotPLus Software was developed with different delay loads. A total of 109 field tests were performed to test the simulation, compiling the results obtained in each of them. These results gave us parameters that were ordered in a database and analyzed demonstrating that in order to minimize the level of vibrations produced by the blasting of sandstone and andesite rocks and to avoid damages to the primary crusher and POP pool, Load factor and optimum output sequence; Made with Montecarlo modeling. And finally after the modeling and simulations for each blast, it was possible to obtain the appropriate parameters for each blasting mesh. In this way, do not exceed the Maximum Permissible Limits of each structure to be controlled.